Stick insect of Taman Negara Johor, Gunung Ledang according to the altitudes - Rabihah I.,; Marwan K.,; Azman S., (Pusat Sistematik Serangga, Fakulti Sains dan Teknologi, Universiti Kebangsaan Malaysia, 2016)
Stick insects (Phasmida) are important herbivores in tropical ecosystem. To date, only few studies that had been conducted on phasmids diversity in Malaysia. We conducted a study on the diversity of phasmids in Gunung Ledang National Park, Johor, Malaysia. Our objective is to determine whether there is a variation in phasmids diversity at different elevation levels. Besides that, this study was aimed to provide an inventory of phasmids in Gunung Ledang for different altitudes. Samplings were denoted by four locations based on altitude i.e. Location L1 (altitude 1000 – 1200m), L2 (700 – 900m), L3 (200 – 350m) and L4 (100 – 120m). Samplings were done by active samplings for every location using torch light between 2000 to 2230 hours during a dark moon phase. This was based on twelve sampling occasions conducted from November 2012 until October 2013. A total of 765 individuals of phasmids comprising 46 species in 22 genera under 5 families (Phasmatidae, 4 spesies in 3 genera; Heteronemiidae, 35 spesies in 15 genera; Aschiphasmatidae, 4 spesies in 1 genus; Bacillidae, 2 spesies in 2 genera; Phyllidae, 1 spesies, 1 genus) has been recorded for Johore National Park, Mount Ledang. The Margalef’s Species Richness index (R’) based on altitude shows the highest at L4 (R’= 4.857) and lowest at L1 (R’ = 3.765). Analysis of Shannon Wiener Diversity Index (H’) following the altitude was highest in altitude L2 (H’ = 2.547) and L3 shows the lowest value (H’ = 1.6). The Evenness Index, E’ = 0.6072 was highest at L4 and lowest at L3 (E’ = 0.1981). Species Accumulation Curve was not reaching the asymptotes; hence, further samplings are needed in order to obtain better results to represent species richness of phasmids for these areas.